2007
DOI: 10.1093/nar/gkm191
|View full text |Cite
|
Sign up to set email alerts
|

Complex translational regulation of BACE1 involves upstream AUGs and stimulatory elements within the 5' untranslated region

Abstract: BACE1 is the protease responsible for the production of amyloid-β peptides that accumulate in the brain of Alzheimer's disease (AD) patients. BACE1 expression is regulated at the transcriptional, as well as post-transcriptional level. Very high BACE1 mRNA levels have been observed in pancreas, but the protein and activity were found mainly in brain. An up-regulation of the protein has been described in some AD patients without a change in transcript levels. The features of BACE1 5′ untranslated region (5′ UTR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
70
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 58 publications
3
70
0
Order By: Relevance
“…One could surmise that these genes are post-transcriptionally regulated to avoid the excess protein that is associated with cytotoxicity and disease. Previous independent studies have reported post-transcriptional regulation for BACE1 (Lammich et al 2004;Mihailovich et al 2007;Hebert et al 2008) and APP Venti et al 2004;Patel et al 2008), in agreement with our data. Fifteen genes were post-transcriptionally up-regulated in at least two cell lines, and GSEA analysis revealed an enrichment for genes that respond to external signals such as viral infection (P = 5.37 3 10 À5 ), and interferon-alpha (P = 1.8 3…”
Section: à5supporting
confidence: 93%
“…One could surmise that these genes are post-transcriptionally regulated to avoid the excess protein that is associated with cytotoxicity and disease. Previous independent studies have reported post-transcriptional regulation for BACE1 (Lammich et al 2004;Mihailovich et al 2007;Hebert et al 2008) and APP Venti et al 2004;Patel et al 2008), in agreement with our data. Fifteen genes were post-transcriptionally up-regulated in at least two cell lines, and GSEA analysis revealed an enrichment for genes that respond to external signals such as viral infection (P = 5.37 3 10 À5 ), and interferon-alpha (P = 1.8 3…”
Section: à5supporting
confidence: 93%
“…Previous studies have supported a role for miRNAs in biologically important partial, as opposed to complete, suppression of target mRNAs (Sevignani et al, 2006;Li et al, 2007). BACE1 genetic regulation is complex (Preece et al, 2003;Lahiri et al, 2006;Li et al, 2006;Rossner et al, 2006;Mihailovich et al, 2007;Stockley and O'Neill, 2007;Tesco et al, 2007) and has been shown to occur partly posttranscriptionally (Marambaud et al, 1998;Rossner et al, 2006). Different regulatory mechanisms probably overlap in time and in cytoplasmic domains with multiple transcriptional, translational, and posttranslational processes involved in BACE1 regulation.…”
Section: Non-demented-case1mentioning
confidence: 94%
“…analysis revealed that the ADAM10 mRNA contains a long 5Ј-UTR with similar properties as the 5Ј-UTR of BACE1, which was shown to be involved in translational repression of BACE1 (32)(33)(34)(35)(36). The 5Ј-UTR of ADAM10 was cloned from a human macrophage cDNA library (41) and contains 444 nucleotides, has a high GC content (69%), and has two uORFs.…”
Section: Adam10 Transcripts Contain a Gc-rich 5ј-utr-sequencementioning
confidence: 99%
“…Among these, BACE1 protein expression was shown to be significantly repressed by its 5Ј-UTR (32)(33)(34)(35)(36). It was demonstrated that the GC-rich region within the BACE1 5Ј-UTR forms a translational barrier that may impede scanning of the ribosome along the 5Ј-UTR or initiate translation (34).…”
mentioning
confidence: 99%
See 1 more Smart Citation